Pseudocapacitance behavior induced double-ion selective HCDI system based on MoS2 / PPy / / Ag-coated PANI / AC and application
By using MoS2/PPy composite materials and Ag@PANI/AC composite materials in the HCDI system, the problems of poor conductivity and poor Cl-removal performance of MoS2 are solved, and efficient dual-ion selective capacitance deionization performance is achieved.
Patent Information
- Application Number
- CN202411589455.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Existing HCDI systems perform poorly in removing Cl-ions, and the poor conductivity and prone agglomeration of MoS2 limit their application, resulting in limited desalination capacity and ion removal rate.
MoS2/PPy composite material is used as the cathode, PPy is used as the growth substrate to reduce interlayer agglomeration of MoS2 nanosheets, and Ag@PANI/AC composite material is used as the anode to construct a 3D conductive structure by modifying polyaniline modified activated carbon by Ag particles to achieve Selective removal of Cl-.
Efficient Na+ and Cl-ion removal was achieved, and the desalination performance was improved, showing an adsorption capacity of 25.1 mg·g-1, a desalination rate of 5.88 mg·g-1·min-1 and a cycling stability of 97.7%.
Smart Images

Figure CN119390196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC and its application. Background Art
[0002] With the growth of global population and the expansion of industrial scale, the impact of freshwater crisis on social progress is becoming more and more serious. The use of unconventional water resources (such as seawater, brackish water and mine water) is essential to meet the daily freshwater demand. Capacitive deionization (CDI) is an emerging electrochemical control technology with the characteristics of environmental friendliness, simple operation and low energy consumption, and has attracted extensive attention in the water purification process. However, the physical charge adsorption based on the electric double layer (EDL) mechanism limits the improvement of desalination capacity, and conventional CDI with porous carbon electrodes has encountered a bottleneck in future development. As the most promising derivative of CDI, hybrid capacitive deionization (HCDI) consists of a faradaic cathode and a carbon anode, which has been widely used in the field of electrochemical desalination. Specifically, the faradaic electrode material selectively removes ions through ion intercalation or interaction with ions via surface redox reactions, thereby achieving high desalination capacity. On this basis, a series of Faraday electrode materials have been proposed, such as transition metal oxides (TMOs), transition metal carbides / nitrides, transition metal dichalcogenides (TMDs), conductive polymers, Prussian blue (PB) and its analogues (PBAs) (cathode materials) and Ag, Bi (anode materials).
[0003] Among these Faraday electrode materials, graphene-like molybdenum disulfide (MoS2), as a typical two-dimensional (2D) layered intercalation material, has attracted the interest of many researchers due to its flexible and adjustable interlayer space, abundant active sites, and high theoretical capacity. However, pure MoS2 is prone to agglomeration and structural collapse, and suffers from poor conductivity in electrochemical applications. Combining MoS2 with carbonaceous materials (such as g-C3N4, graphene, and carbon nanotubes) provides a feasible strategy to overcome these limitations, and the adsorption capacity (SAC) is reported to be 16.8-24.5 mg·g -1 . In addition, the potential volume expansion during the ion intercalation of MoS2 still restricts its further application. Exploring the use of 2D / 3D conductive materials as growth substrates to alleviate the interlayer agglomeration of MoS2 nanosheets while improving their conductivity and stability may become an ideal solution. Conductive polymers, such as polyaniline (PANI) and polypyrrole (PPy), are rich in amine and imine functional groups, have good conductivity, are easy to synthesize, and have high pseudocapacitance, and are expected to improve the CDI performance of MoS2. Excitingly, the nanotubular PPy with a hollow conductive structure helps to build a conductive network, and the unique hollow structure allows the formation of a conductive network in the presence of Na+ It buffers the volume strain of MoS2 during the embedding / removal process, which is considered to be an ideal scaffold for supporting and stabilizing MoS2.
[0004] Currently, almost all HCDI-related system research focuses on Na + Development of capture electrode materials. - The exploration of high-performance anode materials with adsorption has been largely neglected. Porous carbon, a commonly used cathode material, shows low Cl - The removal capacity of SAC is limited to 5 to 10 mg g due to its low capacitance. -1 In MoS2-based HCDI systems, the unbalanced module structure inevitably leads to severe performance mismatch and limits its desalination capacity and ion removal rate. Usually, an anion exchange membrane is also required to be placed on the carbon electrode to alleviate the common ion rejection effect in order to achieve high charge efficiency. In order to solve the above problems, metal-loaded carbon-based materials are considered to be a promising method for selectively capturing Cl - Recently, Vengatesan et al. developed a method for capturing Na + Sepiolite-intercalated graphene (GS) capacitive electrodes and a novel method for selective capture of Cl - The silver-doped GS (AGS) Faraday electrode provided 20.7 mg·g -1 The excellent SAC value and high charge efficiency of 87.1% were achieved. Subsequently, Mittal et al. designed a dual-ion HCDI system using 3D MnO2@graphene / CNT (MGG) and Ag@graphene / CNT (AGG) redox active materials as the negative electrode and positive electrode, respectively. The MGG / / AGG system achieved 62.4 mg·g -1 The high desalination capacity and charge efficiency of up to 95% were achieved. However, the non-conductivity of the formed AgCl hindered the Cl - The further diffusion and electron transport of Ag / AgCl electrodes are affected. Summary of the invention
[0005] In order to overcome the limitations of MoS2's unsatisfactory conductivity, low removal rate and re-deposition tendency, and to solve the kinetic mismatch problem of HCDI, the present invention provides a dual-ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC.
[0006] The dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC provided by the present invention uses a MoS2 / PPy composite material with a three-dimensional flower chain network structure formed by polypyrrole nanotubes and MoS2 nanoflowers as a cathode, and a heterostructured Ag@PANI / AC composite material formed by Ag particles modified with polyaniline modified activated carbon as an anode.
[0007] The preparation method of the MoS2 / PPy composite material is as follows: dissolving ammonium molybdate and thiourea in deionized water, then adding polypyrrole nanotubes, transferring to a high-pressure reactor after ultrasonic treatment, reacting at 160-220°C for 20-30 hours, and washing the obtained black powder with deionized water and anhydrous ethanol by centrifugation and vacuum drying to obtain a MoS2 / polypyrrole composite material, i.e., a MoS2 / PPy composite material. Among them, the mass ratio of the polypyrrole nanotubes to ammonium molybdate and thiourea is preferably 1:1.5-2:2.5-3.5. It is further preferred to react at 190-200°C for 24 hours.
[0008] The preparation method of the polypyrrole nanotubes is as follows: dissolving methyl orange in deionized water by ultrasonic, then adding pyrrole and ferric chloride aqueous solution under stirring conditions, in situ polymerization reaction for 20 to 24 hours in a dark ice bath, filtering and collecting the precipitate after the reaction, washing with deionized water and ethanol, and drying to obtain polypyrrole nanotubes. Preferably, the mass ratio of methyl orange to pyrrole and ferric chloride is 1:2 to 2.5:5 to 5.5.
[0009] The preparation method of the Ag@PANI / AC composite material is as follows: disperse polyaniline modified activated carbon in deionized water, add silver nitrate aqueous solution and stir for 1 to 2 hours, then add ascorbic acid aqueous solution, continue stirring for 2 to 4 hours, finally wash the reaction product with deionized water and dry it to obtain heterogeneous structure Ag loaded polyaniline modified activated carbon, i.e., Ag@PANI / AC composite material. Preferably, the mass ratio of the polyaniline modified activated carbon to silver nitrate and ascorbic acid is 1:0.12 to 0.14:0.13 to 0.15.
[0010] The preparation method of the polyaniline modified activated carbon is as follows: aniline and activated carbon are added to a 1M HCl aqueous solution, ultrasonically treated for 1 to 2 hours, and then an ammonium persulfate aqueous solution is added. After continuous stirring at room temperature for 20 to 24 hours, the resulting precipitate is washed with deionized water and ethanol until the pH value of the filtrate is neutral, and then vacuum dried to obtain polyaniline modified activated carbon. Preferably, the mass ratio of aniline to activated carbon to ammonium persulfate is 1:0.9 to 1.2:1.3 to 1.5.
[0011] The present invention also provides the use of the above-mentioned dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC in water desalination. In this system, hollow PPy nanotubes are anchored by ultrathin MoS2 nanosheets, which serve as conductive chains to connect loose MoS2 nanoflowers to form a 3D flower chain network. PPy as a growth substrate can reduce the stacking of MoS2 nanosheet layers and provide a convenient charge transfer channel. Ag@PANI / AC is synthesized by modifying Ag particles on a 3D electronic conductive substrate formed by coupling PANI and AC. - The conversion reaction occurs to achieve the selective removal of Cl-. The unique electrode material structure design and module configuration optimization can achieve good desalination performance.
[0012] The present invention constructs an advanced pseudocapacitive behavior-induced dual ion selective HCDI system (denoted as Di-CDI system) based on MoS2 / PPy / / Ag@PANI / AC, and introduces Faradaic reactions on two electrodes to remove Na + and Cl - In the Di-CDI system, the PPy conductive network is used as a growth skeleton to alleviate the aggregation of MoS2 nanosheets, providing enhanced conductivity and shortened ion diffusion paths. At the same time, the hollow PPy nanotubes are wrapped by MoS2 nanosheets to form a core-shell structure, which acts like a conductive chain, connecting the loose MoS2 nanoflowers to construct a unique flower chain network. The improved dispersion and enlarged interlayer spacing of MoS2 nanosheets provide Na + The PPy network provides abundant accessible sites for embedding and extraction. The PPy network provides interconnected conductive channels, enabling convenient electron transfer paths and fast charge transport. The charge redistribution at the heterojunction interface catalyzes a strong local electric field, leading to accelerated ion diffusion dynamics. The highly interwoven conductive network enables rapid electron transfer between MoS2 nanoflowers while further enhancing the stability of the heterostructure. As a cathode material, it can achieve Na + Efficient transmission and capture of Cl - The capture material was prepared by coupling polyaniline (PANI) and activated carbon (AC) by in situ polymerization to construct a 3D conductive structure, and then Ag particles were modified on its surface by chemical reduction to synthesize a heterogeneous structure Ag@PANI / AC composite material. -A conversion reaction occurs to produce AgCl. The doped PANI and Ag provide abundant pseudocapacitive reaction sites, which help to generate additional storage capacity. This structural design compensates for the low conductivity of AgCl while providing fast performance and high desalination capacity, thereby achieving rapid electrosorption kinetics. Therefore, the Di-CDI system shows advantages over most published MoS2-based CDI systems. In particular, the ion removal mechanism is revealed by in situ characterization and density functional theory (DFT) calculations. The MoS2 / PPy electrode induces Na + In addition, through the redox-active Ag, the synergistic effect of the Faradaic pseudocapacitive reaction from PAIN and the EDL electrosorption from AC, Cl - Electrochemically adsorbed on the Ag@PANI / AC electrode.
[0013] The beneficial effects of the present invention are as follows:
[0014] 1. The present invention uses MoS2 / PPy as Na + Intercalation cathode, Ag loaded polyaniline modified activated carbon (Ag@PANI / AC) as Cl - By capturing the anode, an asymmetric dual ion-selective capacitive deionization (Di-CDI) system induced by pseudocapacitive behavior was constructed, which effectively solved the performance mismatch problem and further improved the desalination performance.
[0015] 2. The present invention uses the core-shell structure of MoS2 / PPy as a conductive chain to connect loose MoS2 nanoflowers to construct a unique flower chain network. The highly cross-linked conductive network can quickly transfer electrons between MoS2 nanoflowers and further enhance the stability of the heterogeneous structure.
[0016] 3. The present invention couples polyaniline (PANI) and activated carbon (AC) by in-situ polymerization to construct a 3D conductive structure, and loads Ag particles on its surface by chemical reduction to synthesize the Ag@PANI / AC heterostructure. This structure makes up for the low conductivity of AgCl to improve the conductivity and structural stability of the overall structure, and obtains an electrode with ion selectivity, high rate performance and desalination ability.
[0017] 4. The Di-CDI system MoS2 / PPy / / Ag@PANI / AC constructed by the present invention showed a conductivity of 25.1 mg·g -1 Excellent adsorption capacity and excellent desalination rate (5.88 mg g -1 ·min -1 ), good cycling stability (97.7% retention) and improved charge efficiency (56.2%).
[0018] 5. The MoS2 / PPy electrode in the Di-CDI system constructed by the present invention induces Na + In addition, through the synergistic effect of the Faradaic pseudocapacitive reaction between redox-active Ag and PAIN and the electrical double layer (EDL) adsorption of AC, Cl - Electrochemically adsorbed on the Ag@PANI / AC electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 SEM image of MoS2 (a); SEM and TEM (inset) images of PPy nanotubes (b); SEM (c, d), transmission electron microscopy (e) and HRTEM images (f) of MoS2 / PPy (inset: SAED diffraction); elemental mapping of MoS2 / PPy (g~l).
[0020] Figure 2 XRD patterns (a), Raman spectra (b), N2 adsorption / desorption isotherms (c), and pore size distribution diagram (d) of MoS2, PPy nanotubes, and MoS2 / PPy.
[0021] Figure 3 SEM images of AC (a) and PANI / AC (b); SEM image of Ag@PANI / AC-1.2 (c) and corresponding elemental mapping (d~g).
[0022] Figure 4 are the XRD patterns of AC, PANI / AC and Ag@PANI / AC-1.2.
[0023] Figure 5 CV curves of MoS2, PPy nanotubes and MoS2 / PPy (5 mV s -1 )(a) Corresponding specific capacitance (5-100mV s -1 )(b), GCD curve (1A g -1 )(c) Corresponding discharge specific capacitance (0.5~5A g -1 )(d), Nyquist plot (inset: equivalent circuit) (e) and charging resistance of the electrode (f).
[0024] Figure 6 CV curves (5 mV s -1 )(a) Corresponding specific capacitance (5-100mV s -1 )(b), GCD curve (1A g -1)(c) Corresponding discharge specific capacitance (0.5~5A g -1 )(d).
[0025] Figure 7 It is the Nyquist plot of AC, PANI / AC and Ag@PANI / AC-1.2 electrodes.
[0026] Figure 8 The SAC and charge efficiency of the modules MoS2 / / AC, MoS2 / / Ag@PANI / AC and MoS2 / PPy / / Ag@PANI / AC at different voltages (0.8-1.4 V) (a), the change of SAC with time at 1.4 V (b), the corresponding Kim-Yoon plot (c) and the charge efficiency at different NaCl concentrations (100-500 mg·L -1 ) under SACs(d).
[0027] Fig. 9 The SAC variation of the module MoS2 / PPy / / Ag@PANI / AC in the entire concentration range (a) and the corresponding Kim-Yoon plot (b).
[0028] Fig.10 The cyclic stability of the module MoS2 / PPy / / Ag@PANI / AC within 10 adsorption / desorption cycles.
[0029] Fig.11 Comparison of the deionization performance (a) and ion removal rate (b) of the Di-CDI system MoS2 / PPy / / Ag@PANI / AC with the reported MoS2-based CDI system. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0031] Example 1
[0032] 1. Preparation of MoS2 / PPy composite materials
[0033] Step 1: 1.5 g of methyl orange (MO) was placed in 400 mL of deionized water and completely dissolved by ultrasonic treatment, and then 3.5 g of pyrrole (Py) was added dropwise under stirring; subsequently, 13.5 g of FeCl3·6H2O was completely dissolved in 50 mL of deionized water and slowly poured into the resulting Mo / Py solution, and the polymerization reaction was carried out in an ice bath in a dark environment and stirred for 24 h. Finally, the precipitate was collected by filtration, rinsed with deionized water and ethanol to remove MO, and dried at 60 ° C to obtain polypyrrole (PPy) nanotubes.
[0034] Step 2: 0.93 g (NH4)6Mo7O 24 4H2O and 1.71g thiourea were dissolved in 40mL deionized water, and then 0.56g PPy nanotubes were added. After ultrasonic treatment for 60min, the mixture was transferred to an autoclave and kept at 200℃ for 24h. The cooled black powder was washed by centrifugation with deionized water and anhydrous ethanol (3 times), and then dried in vacuo at 60℃ to obtain a MoS2 / PPy composite material with a 3D flower chain network structure.
[0035] In addition, flower-shaped pure MoS2 was synthesized by the same method without doping PPy nanotubes.
[0036] 2. Preparation of Ag@PANI / AC composites
[0037] Step 1: 1.0 g of aniline (PANI) and 1.0 g of activated carbon (AC) were dispersed in 100 mL of 1 M HCl aqueous solution and ultrasonically treated for 2 h. Then, 1.46 g of ammonium persulfate dissolved in 10 mL of deionized water was added dropwise to the above solution. After continuous stirring at 25 °C for 24 h, the black precipitate was filtered and repeatedly rinsed with deionized water and ethanol until the pH value of the filtrate was close to 7. The final product was vacuum dried at 60 °C to obtain polyaniline modified activated carbon (PANI / AC).
[0038] Step 2: Disperse 1.2 g PANI / AC in 40 mL deionized water, add 9.3 mL 0.1 M AgNO3 aqueous solution and stir vigorously for 2 h, then add 10 mL 0.1 mol·L -1 The L-ascorbic acid aqueous solution was stirred for 3 h to reduce the Ag + ; Finally, the reaction product was thoroughly washed with deionized water to remove unreacted chemicals and dried at 60 °C to obtain Ag@PANI / AC (denoted as Ag@PANI / AC-1.2).
[0039] In this example, the amount of PANI / AC added in step 4 was changed to obtain samples containing different amounts of PANI / AC added (1, 1.2 and 1.4 mg), which were labeled as Ag@PANI / AC-x, where x represents the content of PANI / AC.
[0040] like Figure 1 As shown in a, the pristine MoS2 shows dense flower-like microspheres formed by stacking of many intertwined nanosheets. Figure 1 b It can be seen that the PPy nanotubes prepared in this example are cross-linked to form a 3D framework structure. It is worth noting that for a single PPy nanotube ( Figure 1b) shows that it has a relatively smooth surface, and especially the unique hollow structure can provide a large specific surface area (SSA) for fast ion migration and alleviate the Na + Change in overall volume caused by insertion / extraction. Figure 1 d shows that the ultrathin MoS2 nanosheets with good dispersion have been successfully anchored on the surface and around the nanotubular PPy. In addition, TEM observation ( Figure 1 e) It was confirmed that the flower-like MoS2 nanosheets as shells were interconnected, while the single PPy nanotube as the core was wrapped by the MoS2 nanosheets, forming a unique core-shell tubular structure. Figure 1 f shows a high-resolution TEM image of MoS2 nanosheets supported on PPy, showing clear lattice fringes with an enlarged interlayer spacing (0.69 nm) corresponding to the (002) crystal plane. The inset shows the selected area electron diffraction pattern (SAED), indicating that MoS2 / PPy displays a polycrystalline nature with five diffraction rings. EDS image ( Figure 1 e to Figure 1 j) reveals that C, N, O, Mo, and S are uniformly distributed throughout the heterostructure. The presence of PPy is clearly confirmed by the additional N element. In this structure, the PPy nanotubes wrapped by MoS2 nanosheets act as conductive links for electron transfer between the well-dispersed MoS2 nanoflowers ( Figure 1 c). The 3D interconnected flower chain network structure is formed by the interweaving of core-shell tubular PPy and MoS2 nanoflowers.
[0041] exist Figure 2 In a, the broad peak of PPy nanotubes at 2θ = 26.0° corresponds to amorphous PPy. The typical peaks of 2H-MoS2 were observed in MoS2 / PPy, which are located at 14.3°, 33.6°, 39.6°, 49.7° and 59.2°, respectively, and are denoted as (002). 2H 、(101) 2H 、(103) 2H 、(105) 2H and (110) 2H (JCPDS No.37-1492). The (002) peak at 2θ=14.25° in MoS2 shifts to the left to 13.7° in MoS2 / PPy, proving the expansion of the interlayer spacing caused by the interaction between MoS2 and PPy. In addition, the (002) and (101) diffraction peaks in the heterostructure spectrum become broadened, indicating that PPy nanotubes reduce the crystallinity of MoS2. Figure 2 Raman spectra of b show that for MoS2 / PPy and PPy, two significant peaks correspond to the sp 3 Hybrid D band (1356 cm -1 ) and sp2 Hybrid G band (1584cm -1 ). The intensity ratio of the D and G peaks of MoS2 / PPy (I D / I G =0.87) is higher than that of PPy (0.41), indicating that increased structural defects as active sites are formed in the MoS2 / PPy heterostructure. -1 The main peaks of E 1 2g and A 1g Band correlation. 1 2g The band reflects the in-plane transfer of Mo-S, while the A 1g It is generated by the out-of-plane symmetry transfer of S atoms. 1g The peak shifts to the left to 403 cm -1 , proving that the interlayer spacing of MoS2 increases. Figure 2 c results, all samples show type IV isotherms with H3-type hysteresis loops, indicating that mesopores dominate the pore structure. The order of specific surface area is MoS2 (7.8 m 2 g -1 ) <MoS2 / PPy(25.3m 2 g -1 ) <PPy(55.9m 2 g -1 ). Figure 2 d shows that all three samples have mesoporous and macroporous characteristics, and the pore volume order is MoS2 (0.04 cm 3 g -1 ) <MoS2 / PPy(0.14cm 3 g -1 ) <PPy(0.30cm 3 g -1 ). The results show that the introduction of PPy nanotubes together with the dispersed layered MoS2 nanosheets endows the heterostructure with higher SSA and pore volume than that of pristine MoS2.
[0042] like Figure 3 As shown in a, AC exhibits a relatively smooth stone-like morphology with irregular shapes. The in situ polymerization growth of PANI on the surface of AC particles exhibits a nanowire-like external morphology, which is similar to a conductive wire, connecting individual AC particles together to form a 3D interconnected pore structure ( Figure 3 b). Figure 3 c and the corresponding element diagram ( Figure 3 d to Figure 3 g) The results reflect the successful modification of Ag particles on the PANI / AC plane.
[0043] like Figure 4 As shown in XRD, the two broad peaks of AC at 23.9° and 42.4° are related to the (002) and (101) crystal planes of carbonaceous materials, respectively. After in situ polymerization of PANI on the AC surface, the PANI / AC composite overlaps with the 42.4° peak of AC, while the three additional peaks at 14.9°, 20.6°, and 25.2° are related to the (011), (020), and (200) crystal planes of PANI, respectively. For Ag@PANI / AC-1.2, in addition to the typical peaks of PANI, the new peaks at 38.1°, 44.3°, 64.4°, and 77.5° are related to the Ag@PANI / AC-1.2, respectively. 0 The (111), (200), (220) and (311) crystal planes of (JCPDS No. 04-0783) match each other. The presence of these diffraction peaks means that Ag is successfully doped into the heterostructure by chemical reduction.
[0044] Figure 5 a reacted 5mV·s -1 CV curves of MoS2, PPy and MoS2 / PPy electrodes at different scan rates. It is noted that MoS2 / PPy exhibits the largest CV integrated area, and the corresponding specific capacitance is calculated to be 105.22 F g -1 , exceeding MoS2 (37.17F·g -1 ) and PPy(86.90F·g -1 ). In addition, through 5 ~ 100mV·s -1 Comparative analysis of CV curves within the scanning rate range ( Figure 5 b), revealing that the specific capacitance of the three electrodes decreases significantly with the increase of scan rate, and MoS2 / PPy always maintains the highest capacitance characteristics. Observe the GCD curves of the three electrodes ( Figure 5 c) at 1A·g -1 At the current density, the discharge time of MoS2 / PPy is significantly longer than that of the other two electrodes. Figure 5 d depicts the relationship between discharge specific capacitance and current density. The charge and discharge time increases with the current density (0.5~5A·g -1 ) increases. MoS2 / PPy maintains its advantage in all density ranges, which is consistent with the CV results. These findings indicate that the introduction of PPy nanotubes improves the pseudocapacitive electrochemical performance of the MoS2 / PPy electrode. The impedance characteristics of the three electrodes were studied by the AC impedance method. According to the equivalent circuit simulation R s (interface resistance) and R ct (Charge transfer resistance)( Figure 5 e). R of MoS2, PPy and MoS2 / PPy electrodes sThe values are 2.89Ω, 2.55Ω and 2.48Ω respectively. In addition, R ct (MoS2 / PPy)=1.76Ω <R ct (PPy)=2.08Ω <R ct (MoS2) = 5.03Ω. Figure 5 f, MoS2 / PPy electrode shows lower charging resistance compared with MoS2 and PPy electrodes, further verifying that the unique 3D flower chain network structure of MoS2 / PPy can promote charge transfer and ultimately induce rapid Na + storage.
[0045] AC, PANI / AC, Ag@PANI / AC-1, Ag@PANI / AC-1.2, and Ag@PANI / AC-1.4 electrodes at 5 mV s -1 The CV curve under the sweep rate is as follows Figure 6 a. The enclosed area of Ag@PANI / AC-1.2 is the largest, and the corresponding specific capacitance is calculated to be 192.06 F·g -1 , significantly higher than AC (120.48F·g -1 )、PANI / AC(151.41F·g -1 )、Ag@PANI / AC-1(180.21F·g -1 ) and Ag@PANI / AC-1.4(169.72F·g -1 In Ag@PANI / AC-x, another pair of strong redox peaks appeared near -0.05 and 0.21 V, representing the Ag / Ag + Reversible electrochemical transformation of Figure 6 As shown in (b), the specific capacitance of the five electrodes decreases significantly with the increase of the scan rate. At any scan rate, the specific capacitance of Ag@PANI / AC-x is higher than that of PANI and AC. In particular, Ag@PANI / AC-1.2 performs best in the entire scan rate range. From the GCD curves of the five electrodes ( Figure 6 c), it is clearly observed that the charge and discharge times increase with increasing current density (0.5-5 A·g -1 ) and gradually decreases. The discharge time of Ag@PANI / AC-1.2 is significantly longer than that of AC, PANI / AC, Ag@PANI / AC-1, and Ag@PANI / AC-1.4, indicating its advantages in charge release and storage capacity. At the same time, the specific capacitance of Ag@PANI / AC-1.2 maintains an advantage in all density ranges ( Figure 6 d). By fitting the equivalent circuit ( Figure 7 ), R of AC, PANI / AC and Ag@PANI / AC-1.2 electrodes sThe values are 3.58Ω, 3.08Ω, and 3.06Ω respectively. In addition, R ct (Ag@PANI / AC-1.2)=0.64Ω <R ct (PANI / AC)=0.95Ω <R ct (AC) = 5.81Ω. This indicates that appropriate Ag loading helps to reduce the ion transport resistance at the interface between the Ag@PANI / AC-1.2 heterostructure and the electrolyte, thereby improving the conductivity of the electrode and obtaining the desired ion diffusion capacity.
[0046] Based on the comparison of electrochemical performance, Ag@PANI / AC-1.2 was selected as the best electrode to be assembled into the Di-CDI system. Three asymmetric desalination systems were configured, including a HCDI system constructed with MoS2 / / AC and two Di-CDI systems: MoS2 / / Ag@PANI / AC and MoS2 / PPy / / Ag@PANI / AC. The effect of working voltage on deionization performance was first studied at 500 mg·L -1 The evaluation was performed in NaCl solution ( Figure 8 a). When the voltage increases from 0.8 to 1.4 V, the SAC of the MoS2 / PPy / / Ag@PANI / AC system always shows an advantage over the other two systems. As the voltage increases, the charge efficiency of the three systems shows a downward trend. At a voltage of 0.8 V, the maximum electrical efficiencies of MoS2 / PPy / / Ag@PANI / AC and MoS2 / / Ag@PANI / AC are 56.2% and 50.8%, respectively, which are higher than the maximum charge efficiency of MoS2 / / AC (42.7%). Figure 8 In b, MoS2 / PPy / / Ag@PANI / AC reached adsorption equilibrium with the fastest removal rate and obtained the largest SAC (25.1 mg·g -1 ), MoS2 / / Ag@PANI / AC(18.2mg·g -1 ) and MoS2 / / AC (13.9 mg·g -1 ) is 1.38 and 1.81 times. Figure 8 In the Kim-Yoon plot of (c), the relationship between adsorption rate (SAR) and SAC intuitively describes the ion removal performance. It is obvious that at 1.4 V, the curve of MoS2 / PPy / / Ag@PANI / AC occupies the upper right quadrant, indicating the largest SAC (25.1 mg·g -1 ) and the fastest SAR (5.88 mg·g -1 ·min -1). Comparing the two Di-CDI systems, MoS2 / PPy / / Ag@PANI / AC exhibited better deionization ability than MoS2 / / Ag@PANI / AC. Based on the comparison results of SAC, the optimal voltage was determined to be 1.4 V. - 1 Comparison of the SAC of MoS2 / PPy / / Ag@PANI / AC in the NaCl concentration range ( Figure 8 d). As can be observed, the SAC of MoS2 / PPy / / Ag@PANI / AC gradually increases from 11.3 to 15.2, 17.4, 21.0, and 25.1 mg·g, respectively. -1 , which is higher than the other two systems at any concentration. With the increase of concentration, the SAC of the three systems shows an upward trend. Fig. 9 a reveals that the SAC of MoS2 / PPy / / Ag@PANI / AC shows the same trend under different NaCl concentrations, which increases significantly in the initial stage and then rises slowly until it approaches saturation, and the corresponding Kim-Yoon diagram Fig. 9 b. Obviously, 500 mg·L - 1 The curve of NaCl is located in the upper right corner, showing the best ion removal ability.
[0047] The cycling stability of MoS2 / PPy / / Ag@PANI / AC is 1.4 V and 300 mg·L -1 The conductivity change curve ( Fig.10 ) It can be seen that after 10 consecutive charge / discharge cycles, 97.7% of the adsorption capacity is still maintained, indicating that the Di-CDI system has significant cyclability. The desalination capacity of MoS2 / PPy / / Ag@PANI / AC is compared with various previously reported MoS2-based CDI systems ( Fig.11 a and 11b). The Di-CDI system MoS2 / PPy / / Ag@PANI / AC exhibits competitive SAC, especially the ultrafast rate capability surpassing other reported MoS2-based HCDI and symmetric CDI systems.
[0048] In summary, the present invention constructs a Di-CDI system, which contains a 3D interconnected flower chain network MoS2 / PPy as Na + Capture electrode, a 3D conductive structure Ag@PANI / AC as Cl - Capture electrode. Thanks to the unique design of electrode materials and the optimization of module configuration, the MoS2 / PPy / / Ag@PANI / AC system exhibited an excellent desalination capacity (25.1 mg g-1 ), ultra-high maximum ion removal rate (5.88 mg·g -1 ·min -1 ) and good desalination retention (97.7% after 10 cycles). The MoS2 / PPy electrode induces Na + Similarly, through the redox-active Ag, the synergistic effect of the Faradaic pseudocapacitive reaction from PAIN and the EDL electrosorption from AC, Cl - It is electrochemically adsorbed on the Ag@PANI / AC electrode. Therefore, the MoS2 / PPy composite material and the Ag@PANI / AC composite material prepared by the present invention can become promising candidate materials for seawater desalination and construct a Di-CDI system for water purification.
Claims
1. A dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC, characterized in that: The HCDI system uses a MoS2 / PPy composite material with a three-dimensional flower chain network structure formed by polypyrrole nanotubes and MoS2 nanoflowers as a cathode, and a heterogeneous structure Ag@PANI / AC composite material formed by Ag particles modifying polyaniline modified activated carbon as an anode; The preparation method of the MoS2 / PPy composite material is as follows: ammonium molybdate and thiourea are dissolved in deionized water, polypyrrole nanotubes are added, and after ultrasonic treatment, the mixture is transferred to a high-pressure reactor, and reacted at 160-220° C. for 20-30 hours. The obtained black powder is centrifugally washed with deionized water and anhydrous ethanol and then vacuum dried to obtain a MoS2 / polypyrrole composite material, i.e., a MoS2 / PPy composite material. The preparation method of the Ag@PANI / AC composite material is as follows: dispersing polyaniline modified activated carbon in deionized water, adding silver nitrate aqueous solution and stirring for 1 to 2 hours, then adding ascorbic acid aqueous solution, continuing to stir for 2 to 4 hours, and finally washing the reaction product with deionized water and drying to obtain a heterogeneous structure of Ag-loaded polyaniline modified activated carbon, i.e., Ag@PANI / AC composite material.
2. The dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC according to claim 1, characterized in that: In the preparation method of the MoS2 / PPy composite material, the mass ratio of polypyrrole nanotubes to ammonium molybdate and thiourea is 1:1.5-2:2.5-3.
5.
3. The dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC according to claim 1, characterized in that: In the preparation method of the MoS2 / PPy composite material, the reaction is carried out at 190-200°C for 24 hours.
4. The dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC according to any one of claims 1 to 3, characterized in that: The preparation method of the polypyrrole nanotubes comprises: dissolving methyl orange in deionized water by ultrasonic wave, then adding pyrrole and ferric chloride aqueous solution under stirring conditions, carrying out in-situ polymerization reaction for 20 to 24 hours in a dark ice bath, collecting the precipitate by filtering after the reaction, washing with deionized water and ethanol, and drying to obtain the polypyrrole nanotubes.
5. The dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC according to claim 4, characterized in that: In the preparation method of the polypyrrole nanotubes, the mass ratio of methyl orange to pyrrole and ferric chloride is 1:2-2.5:5-5.
5.
6. The dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC according to claim 1, characterized in that: In the preparation method of the Ag@PANI / AC composite material, the mass ratio of polyaniline-modified activated carbon to silver nitrate and ascorbic acid is 1:0.12-0.14:0.13-0.
15.
7. The dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC according to claim 1 or 6, characterized in that: The preparation method of the polyaniline modified activated carbon is as follows: aniline and activated carbon are added to a 1M HCl aqueous solution, ultrasonically treated for 1 to 2 hours, and then an ammonium persulfate aqueous solution is added. After continuous stirring at room temperature for 20 to 24 hours, the obtained precipitate is washed with deionized water and ethanol until the pH value of the filtrate is neutral, and then vacuum dried to obtain the polyaniline modified activated carbon.
8. The dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC according to claim 7, characterized in that: In the preparation method of polyaniline-modified activated carbon, the mass ratio of aniline to activated carbon and ammonium persulfate is 1:0.9-1.2:1.3-1.
5.
9. Use of the dual ion selective HCDI system induced by pseudocapacitive behavior based on MoS2 / PPy / / Ag@PANI / AC as claimed in claim 1 in water desalination.
Citation Information
Patent Citations
Preparation method and application of molybdenum disulfide / polypyrrole supercapacitor electrode material
CN106057498A
Carbon nano tube / polypyrrole / MoS2 composite electrode material, preparation method thereof and CDI desalination application of carbon nano tube / polypyrrole / MoS2 composite electrode material
CN118239573A
High specific capacitance solid state supercapacitor and method of manufacture
US20200286689A1